China primary school students' STEM views, attitudes, self-concept, identity and experiences: A pilot study in Shandong province - Feiyue Wang; Tang Wee Teo; Shoubao Gao (STEM Education)
This article reports the survey findings of a pilot study on primary students' views, attitudes, self-concept, identity, and experiences toward STEM education. This survey was held in China Shandong Province. Applying a mixed-method approach, we administered the survey to 332 students and interviewed 8 students to learn about their views about STEM education after the activity. The survey data was analyzed using Rasch on five constructs, namely views, attitudes, self-concept, identity, and experiences in STEM learning. The transcribed interviews were analyzed using emergent coding. The findings showed that students generally responded positively to the five constructs. Students thought that problem-solving was essential, but it was still difficult for them to solve a real-world problem. They agreed that joining STEM activities could enhance their interest in STEM jobs, but they still had less confidence in pursuing a STEM job. The findings provide some insights into a pilot STEM curriculum work in a province and open up possibilities for broadening and deepening knowledge about STEM teaching and learning in China, which is at its nascent stages.